Rethinking the Built Environment in the Context of Covid-19 Pandemic: A Critical Review - Damla Mısırlısoy; Kağan Günçe (Journal of Architectural Sciences and Applications, 2023)
The built environment should be re-evaluated in the context of Covid-19 pandemic for preventing the spread of the virus. The study aims to reveal the issues that arise in the context of the Covid-19 pandemic at different scales of the built environment, from urban to interior scale and also to emphasize the importance of designing a sustainable environment by considering the lessons learned. The study highlights the significance of designing a sustainable environment by incorporating lessons learned from the pandemic experience. By investigating and highlighting these issues, the research aims to provide recommendations that can guide future efforts towards creating resilient and adaptive built environments. The method of the study is based on the critical review of the published studies on the issue between April 2020-April 2022 and observations on user experiences. The findings of the study highlight the necessity of further questioning the built environment in light of possible pandemics.